2020
DOI: 10.1016/s1470-2045(20)30205-9
|View full text |Cite
|
Sign up to set email alerts
|

Challenges posed by COVID-19 to children with cancer

Abstract: A. Characteristics and outcomes of coronavirus infection in children: the role of viral factors and an immunocompromised state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
128
0
25

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(153 citation statements)
references
References 3 publications
0
128
0
25
Order By: Relevance
“…Pediatric oncology specialists have published recommendations for providing care to children undergoing cancer treatment during the COVID‐19 pandemic 8,22 . They urge continuation of standard aggressive chemotherapy given the curable nature of most pediatric cancers and current evidence, suggesting milder COVID‐19 disease courses in children.…”
Section: Figurementioning
confidence: 99%
“…Pediatric oncology specialists have published recommendations for providing care to children undergoing cancer treatment during the COVID‐19 pandemic 8,22 . They urge continuation of standard aggressive chemotherapy given the curable nature of most pediatric cancers and current evidence, suggesting milder COVID‐19 disease courses in children.…”
Section: Figurementioning
confidence: 99%
“…The current coronavirus disease 2019 (COVID‐19) pandemic has led to numerous changes for all of us, including in pediatric hematology/oncology 1 . Emergency stay at home orders, social distancing, and hygiene measures are all efforts to reduce transmission of this deadly virus.…”
Section: Introductionmentioning
confidence: 99%
“…Older people and people with pre‐existing medical conditions (such as diabetes and heart disease) are more vulnerable to becoming severely ill with the virus. There is a widespread anxiety among families of children with cancer due to the risk of exposure to SARS‐CoV‐2, either in the hospital or community setting 1 . Recently, Ogimi et al reported that infants and younger children (ie, less than 5 years) are more likely to develop severe clinical manifestations than older children, probably due to immaturity of the immune system 2 .…”
Section: Figurementioning
confidence: 99%